Bias byArtificial Intelligence in English Language Teaching: Challenges, Opportunities, and Strategies for Success - Abeywickrama, B. (University of Jaffna, 2025)
Artificial intelligence (AI) is revolutionizing the field of education, transforming teaching practices, learning experiences, and assessment methods. In the field of English language teaching (ELT), it offers numerous advantages to teachers as well as learners including individualized teaching and learning, real-time feedback, and automated assessments. However, concerns about academic integrity and the limitations of AI-driven evaluation methods have prompted scholars to reassess the integration of AI in the field of English language teaching and investigate the need for ethical guidelines to ensure responsible and effective implementation of AI in language classrooms. This research aims to examine how AI can be effectively integrated into English as a second language contexts with a special focus on language assessment. Early research on the role of AI in language education highlighted its advantages and explored measures to ensure equitable opportunities while mitigating potential biases and barriers to adoption. Over time, however, scholarly focus shifted toward addressing challenges associated with AI-assisted teaching and learning. With the increasing use of AI in language teaching, it is essential to examine its integration into language classrooms in ways that foster language learning and academic integrity. Another area worthy of investigation is the effectiveness of plagiarism detection tools and their effectiveness in language testing. This study employs a mixed-methods approach and includes an analysis of AI-assisted learning tools and assessment methods as well as qualitative data from ELT practitioners and learners. The findings emphasize the need to leverage AI for pedagogical advancement and discourage the over-reliance on AI-generated content.
Keywords: Artificial intelligence; English language teaching; Language assessment